2010
DOI: 10.1002/clc.20772
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stem Cell Therapy on Left Ventricular Remodeling After Acute Myocardial Infarction: A Meta‐Analysis

Abstract: Objectives:The objective was to perform a meta-analysis of clinical trials that investigated the effects of stem cell therapy on left ventricular remodeling in patients after acute myocardial infarction (AMI). Background: Intracoronary injection of stem cells in the acute phase of myocardial infarction has been proposed to replace the cardiomyocytes lost and to prevent deleterious pathological remodeling after myocardial infarction. Previously published trials have investigated the effects of cell therapy on l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…3335 Despite the poor retention rates, small improvements in cardiac function and reduction in ventricular scarring have been reported, providing evidence of potential therapeutic utility. 36,37 Such in vivo studies can be challenging and expensive, making it difficult to iteratively test and develop new strategies for improved efficacy. Another common challenge of cell-based therapies is the often-limited source and quantity of the therapeutic cells, which can preclude the use of many conventional adhesion assays, whether in vivo or in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…3335 Despite the poor retention rates, small improvements in cardiac function and reduction in ventricular scarring have been reported, providing evidence of potential therapeutic utility. 36,37 Such in vivo studies can be challenging and expensive, making it difficult to iteratively test and develop new strategies for improved efficacy. Another common challenge of cell-based therapies is the often-limited source and quantity of the therapeutic cells, which can preclude the use of many conventional adhesion assays, whether in vivo or in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, intracoronary cell therapy has been reported to be accompanied with a decrease in incidence of death, recurrent of acute myocardial infarction, and readmission for heart failure 294,297 . At the present time, however, clinical reports regarding the effect of intracoronary stem/progenitor cell treatment on the infarct volume and remodeling remain inconsistent 294,295,297,299 . A phase 3, randomized, double-blinded, active-controlled, unblinded standard of care study (the RENEW study) is underway to assess the efficacy and safety of intramyocardial administration of autologous CD34 + cells in patients with refractory angina 300 .…”
Section: Application Of Vascular Precursor Cells In the Treatment Of mentioning
confidence: 98%
“…To disentangle such a complex subject, a series of metaanalyses (MAs) were conducted during the past 8 years: 12 were focused on patients with acute MI (AMI), [15][16][17][18][19][20][21][22][23][24][25][26] 7 evaluated cell therapy in the context of CIHD, [27][28][29][30][31][32][33] and 4 took into account both conditions. [34][35][36][37] Although, overall, 81% and 92% of MAs on AMI and CIHD, respectively, yielded positive outcomes (Figure 1), it has been recently suggested that published MAs on BMC therapy for IHD far outnumber wellconducted RCTs.…”
Section: Article See P 558mentioning
confidence: 99%